Interaction testing for an ad-hoc system (queue management system) - Ramli R.; Mohamed Zabil M.H.; Lim K.C.; Yusoff Y.; Yusuff M.S. (Asian Research Publishing Network, 2023)
The number of student intake to the university has increased significantly for the past few intakes. In normal condition, newly registered student needs to go through various registration related processes before the registration could be completed. The increment in the number of students has affected the whole registration process that could take hours to complete due to bottleneck condition at some counters. To expedite and smooth the registration process, the Queue Management System (QMS) which is used during the registration day has been revised. In order to increase the confidence level of QMS to be used in real environment setting, the system has been tested using an interaction testing technique to detect as many errors as possible due to interaction. Although the testing activity was done in limited time with inadequate requirement and design documentation, quiet a number of errors have been managed to be detected. During the real environment, no system error was recorded and as the result, the whole registration process takes less time compared to the previous years. The results obtained showed interaction testing is possible to be used in detecting faults given time constraints and lack of requirement documentation. This paper reports how interaction testing is designed and conducted as well as discussing the challenges faced by the researches and strategies to overcome it. 2006-2015 Asian Research Publishing Network (ARPN).